BEHAVIOUR OF SOME ISOLATED AND CONJUGATED UNSATURATED COMPOUNDS, ARENES AND AROMATIC HETEROCYCLES IN A Ni-Al/NaOH REDUCING SYSTEM - Mirela Suceveanu; Matei Raicopol; Adriana Fînaru; Sorin I. Roşca (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this paper we present the results of some experiments in which substrates representing various unsaturated and aromatic systems were tested in reduction reactions with Ni-Al alloy in aqueous NaOH and we highlight the relationships between the structure and the reactivity of the investigated compounds. We have found that unsaturated compounds containing isolated double bonds carbon-carbon and polynuclear condensed ring aromatics present an advanced inertness to the reduction process by the aluminum component of the Ni-Al/NaOH system. Unlike them, unsaturated compounds with C=C conjugated bonds are very reactive to the Ni-Al/NaOH system, 1,4 reduction processes being facilitated, behaviour attributed to the polar nature of the conjugated systems. The heterocyclic compounds have a higher reactivity than their homologues carbocyclic compounds.